Role of Phosphatidylinositol Clathrin Assembly Lymphoid-Myeloid Leukemia (PICALM) in Intracellular Amyloid Precursor Protein (APP) Processing and Amyloid Plaque Pathogenesis - Xiao, Qingli (American Society for Biochemistry and Molecular Biology, 2012)
One of the pathological hallmarks of Alzheimer disease is the accumulation of amyloid plaques in the extracellular space in the brain. Amyloid plaques are primarily composed of aggregated amyloid β peptide (Aβ), a proteolytic fragment of the transmembrane amyloid precursor protein (APP). For APP to be proteolytically cleaved into Aβ, it must be internalized into the cell and trafficked to endosomes where specific protease complexes can cleave APP. Several recent genome-wide association studies have reported that several single nucleotide polymorphisms (SNPs) in the phosphatidylinositol clathrin assembly lymphoid-myeloid leukemia (PICALM) gene were significantly associated with Alzheimer disease, suggesting a role in APP endocytosis and Aβ generation. Here, we show that PICALM co-localizes with APP in intracellular vesicles of N2a-APP cells after endocytosis is initiated. PICALM knockdown resulted in reduced APP internalization and Aβ generation. Conversely, PICALM overexpression increased APP internalization and Aβ production. In vivo, PICALM was found to be expressed in neurons and co-localized with APP throughout the cortex and hippocampus in APP/PS1 mice. PICALM expression was altered using AAV8 gene transfer of PICALM shRNA or PICALM cDNA into the hippocampus of 6-month-old APP/PS1 mice. PICALM knockdown decreased soluble and insoluble Aβ levels and amyloid plaque load in the hippocampus. Conversely, PICALM overexpression increased Aβ levels and amyloid plaque load. These data indicate that PICALM, an adaptor protein involved in clathrin-mediated endocytosis, regulates APP internalization and subsequent Aβ generation. PICALM contributes to amyloid plaque load in brain likely via its effect on Aβ metabolism.